2013
DOI: 10.1007/s11099-013-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in energy dissipation in etiolated wheat seedlings during the greening process

Abstract: We studied the developmental changes in photosynthetic and respiration rates and thermal dissipation processes connected with chloroplasts and mitochondria activity in etiolated wheat (Triticum aestivum L., var. Irgina) seedlings during the greening process. Etioplasts gradually developed into mature chloroplasts under continuous light [190 µmol(photon) m -2 s -1 ] for 48 h in 5-day-dark-grown seedlings. The net photosynthetic rate of irradiated leaves became positive after 6 h of illumination and increased fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Since there was a significant enhancement in the Y(NPQ) in US-1 segments under high PFD compared to low PFD illumination, the photosynthetic apparatus present in the US-1 segment was capable for light acclimation and xanthophyll-cycle based quenching processes, typical to well-operating photosynthetic machineries. Increase in the Y(NPQ) was also found during late stages of the greening process in wheat leaves [52]. Reaction center quenching is a process of primary importance if the acceptor-side processes in the PSII are limited by different reasons [53].…”
Section: Discussionmentioning
confidence: 98%
“…Since there was a significant enhancement in the Y(NPQ) in US-1 segments under high PFD compared to low PFD illumination, the photosynthetic apparatus present in the US-1 segment was capable for light acclimation and xanthophyll-cycle based quenching processes, typical to well-operating photosynthetic machineries. Increase in the Y(NPQ) was also found during late stages of the greening process in wheat leaves [52]. Reaction center quenching is a process of primary importance if the acceptor-side processes in the PSII are limited by different reasons [53].…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that continuous illumination results in a continuous Pchlide photoreduction and Chl formation, which triggers PLB dispersion followed by formation of thylakoid membranes. The greening process is multiphasic and the individual mechanisms involved in energy trapping, protection as well as respiration are sequentially activated [ 21 , 99 , 111 114 ]. First, the photosystems reaction centre cores are assembled, which is followed by a progressive development of complex antenna systems.…”
Section: Discussionmentioning
confidence: 99%
“…First, the photosystems reaction centre cores are assembled, which is followed by a progressive development of complex antenna systems. It was shown that the assembly of the PSII activity started within the first 20 minutes of greening [ 83 ] and took several hours to be completed [ 83 , 111 ]. The formation of PSII reaction centers and their minor antenna components were observed within the first 3–4 hours of deetiolation, whereas LHCII polypeptides started to accumulate after that time [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under excess light conditions, AOX might be involved in the oxidation of excess reductants exported from the chloroplasts (Raghavendra & Padmasree, 2003; Dinakar et al, 2010). It has been reported that increases in respiratory activity, AOX capacity, heat production and AOX1a expression simultaneously occurred in wheat leaves during the first 6–12 h of de‐etiolation (Garmash et al, 2013, 2015). Furthermore, during this period, prolamellar bodies (PLBs) were already converted to thylakoids (Garmash et al, 2013), but PSI and PSII were not completely developed (Garmash et al, 2014a).…”
Section: Activity Of Aox Is Related To Development Of the Photosynthementioning
confidence: 99%
“…It has been reported that increases in respiratory activity, AOX capacity, heat production and AOX1a expression simultaneously occurred in wheat leaves during the first 6–12 h of de‐etiolation (Garmash et al, 2013, 2015). Furthermore, during this period, prolamellar bodies (PLBs) were already converted to thylakoids (Garmash et al, 2013), but PSI and PSII were not completely developed (Garmash et al, 2014a). Respiration and AOX capacity decreased 24 h after de‐etiolation, when clear 77‐K fluorescence emission peaks of PSI (F730) and PSII (F685 and F695) were detected (Garmash et al, 2014a).…”
Section: Activity Of Aox Is Related To Development Of the Photosynthementioning
confidence: 99%